2020
DOI: 10.1177/2050312120944201
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhea and associated factors among under-5 children in Ethiopia: A secondary data analysis

Abstract: Objectives: Diarrhea is a major contributing factor for preventable childhood morbidity and death. Despite the occurrence of diarrhea is decreasing, its effect is increasing at an alarming rate among under-5 children particularly in developing countries. The survey was aimed to assess diarrhea and associated factors among children less than 5 years (0–59 months) in Ethiopia with nationally representative data. Methods: The data were extracted from the Ethiopian National Survey of 2016. A logistic regression mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Inadequate quantities and quality of drinking water and lack of sanitation facilities cause the death of millions of the world’s poorest people through diarrheal diseases each year [ 9 , 10 ]. Furthermore, studies revealed that age of child [ 11 – 15 ], maternal education [ 11 , 12 , 16 ], lack of awareness of mothers/caregivers [ 17 , 18 ], lower socio-economic status [ 12 ], distance and source of drinking water [ 11 , 19 , 20 ], latrine and hand washing facilities [ 21 , 22 ], breast feeding [ 21 , 23 ], place of residence [ 14 , 22 , 24 ], disposal of children’s stool [ 24 26 ], family size [ 17 , 27 ], number of under-five children in the household [ 13 , 18 ], maternal age [ 19 , 20 ] and maternal employment status [ 13 , 17 , 19 , 28 ] as the determinant factors of diarrhea among under-five children.…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate quantities and quality of drinking water and lack of sanitation facilities cause the death of millions of the world’s poorest people through diarrheal diseases each year [ 9 , 10 ]. Furthermore, studies revealed that age of child [ 11 – 15 ], maternal education [ 11 , 12 , 16 ], lack of awareness of mothers/caregivers [ 17 , 18 ], lower socio-economic status [ 12 ], distance and source of drinking water [ 11 , 19 , 20 ], latrine and hand washing facilities [ 21 , 22 ], breast feeding [ 21 , 23 ], place of residence [ 14 , 22 , 24 ], disposal of children’s stool [ 24 26 ], family size [ 17 , 27 ], number of under-five children in the household [ 13 , 18 ], maternal age [ 19 , 20 ] and maternal employment status [ 13 , 17 , 19 , 28 ] as the determinant factors of diarrhea among under-five children.…”
Section: Introductionmentioning
confidence: 99%
“…A systemic review and meta-analysis study done with 31studies revealed that the pooled prevalence of diarrhea among under-ve children in Ethiopia was 22% (18). Many recent local studies also showed the prevalence of diarrhea in under-ve children ranging from 10.2% to 29.9% (19)(20)(21)(22)(23)(24)(25). Diarrheal disease has contributed to 38.4% of deaths from infectious and parasitic diseases and 8% of the total death in Ethiopia (26).…”
Section: Introductionmentioning
confidence: 99%
“…[10] The possibility reasons for diarrhea incidences different from place to place among children included the size of child at birth, type of toilet facility [11], quality of drinking water and lack of hygiene services reason the loss of millions of the world's poorest individuals through diarrheal illnesses each year [12,13]. Additionally, studies shows that age of child [14,15], maternal education [14,16,17], lack of awareness of mothers/caregivers [18,19], lower socio-economic status [16], distance and source of drinking water [14,20,21], latrine and hand washing facilities [22,23], breast feeding [22,24], place of residence [11,23,25], disposal of children's stool [25,26],…”
Section: Introductionmentioning
confidence: 99%